WEARPROOFNESS OF TITANIC ALLOY, FIXED CERAMIC COMPOSITION COVERAGE IN THE CONDITIONS OF FRETTAGE - Лабунець, В.Ф.; Бурбела, Ю.Б. (Science-based technologies, 2009)
In this article the wearproofness of titanic alloy of ВТЗ-1 is considered under conditions of a contact load-ing. The situation analysis and needs in such work have been carried out. The research of the surface strength-ening of this alloy with ceramic composition coverages is also described. The tests results under conditions of frettage at a friction without lubricating material out on the air in the systems „coverage-coverage” and „cov-erage-steel 45” are shown here.